Astragaloside IV Improves Bleomycin-Induced Pulmonary Fibrosis in Rats by Attenuating Extracellular Matrix Deposition - Li, Liu-Cheng; Xu, Liang; Hu, Yan; Cui, Wen-Jie; Cui, Wen-Hui; Zhou, Wen-Cheng; Kan, Lian-Di (Frontiers in Pharmacology, 2017)
Pulmonary fibrosis is a devastating lung disorder with mysterious pathogenesis and limited treatment options. It is well recognized that the uncontrolled proliferation of lung fibroblasts and differentiation of fibroblasts into myofibroblasts excessively produce extracellular matrix (ECM) proteins which contribute to the fibrosis change of the lungs. Thus, blocking ECM accumulation would delay fibrosis progression. In this study, we observed the effects of astragaloside IV (ASV) (10 mg/kg/d) on ECM proteins in bleomycin (BLM, 5 mg/kg)-treated rats. Our results showed that ASV not only ameliorated BLM-induced body weight loss, lung coefficient increase, histological changes and collagen secretion, but also reduced the levels of type III collagen (Col-III) in lung homogenate, laminin (LN) and hyaluronic acid (HA) in serum, as well as hydroxyproline (HYP) in lung tissue. Besides, ASV significantly down-regulated the levels of high-mobility group box1 (HMGB1) in serum and lung tissue, and inhibited the up-regulated expression of α-SMA (marker of myofibroblasts) in the lungs. Taken together, these findings indicate that ASV attenuates BLM-induced ECM deposition, supporting its use as a promising candidate to treat lung fibrosis.